Beginning CSS Web Development From Novice to Professional - Collison, Simon. (Apress : Imprint: Apress, 2006)
Cascading Style Sheets (CSS) are one of the most important technologies on the web today. They give web developers the power to style their web sites so those sites are usable, compact, good looking, consistently displayable, and quick and efficient to change if so desired. There are many books out there on CSS, but Beginning CSS Web Development is different—it doesn't waste time discussing theory, and it delves straight into the practical matter. It provides you with what you need to know, faster. It is also completely up to date, covering the most modern CSS standards and design techniques. In addition to the essential CSS basics, this book covers advanced techniques like accessibility, hacks, and filters. The book concludes with a case study, and features a CSS reference section that allows you to look up required syntax as quickly as possible.